UTILIZATION OF MEDIATION IN MEDICAL DISPUTE SETTLEMENT DURING COVID 19 PANDEMIC - Anggraeni Endah Kusumaningrum (Diponegoro Law Review, 2022)
Health services provided by doctors to patients during the COVID-19 pandemic can lead to medical disputes, such as the case of a patient who feels he has been infected with the virus even though the results of the PCR swab are negative, as well as the refusal of patients who are about to give birth because they have not had a PCR swab. Mediation can be used as an alternative to medical dispute resolution outside the court by involving the mediator in order to achieve a final result that is acceptable to the parties. This study uses a normative juridical approach and secondary data sources as the main data through primary, secondary, and tertiary legal materials and will be analyzed qualitatively. The obligation to carry out mediation in medical disputes is considered a faster and relatively inexpensive dispute resolution process and fulfills a sense of justice as regulated in Article 29 of Law No. 36 of 2009 concerning Health in accordance with Article 130 HIR and Article 154 Rbg that cases that do not take the Mediation procedure are a violation. To the provisions of HIR and Rbg. Similarly, PERMA No. 1/2016 concerning Mediation Procedures in Court as a substitute for PERMA No. 1/2008.